Integrating Strategy-Based Instructions In 7th-Grade Speaking Classroom At SMP Muhammadiyah 2 Batu - Teguh Hadi Saputro; Adityo Adityo; Amalia Ayu Wardhani (University of Muhammadiyah Malang, 2017)
Second language (L2) pedagogy and second language acquisition (SLA) have acknowledged the significant role of learning strategies. It, then, suggests the significance of learning strategies in second language learning or, even, acquisition, especially helping students be better learners. With regard to this, a community service project is proposed to implement this SBI in SMP Muhammadiyah 2 Malang. The students’ problem in speaking ability seems to derive from lacks of knowledge about oral communication strategies (OCSs). Therefore, the project team plans to implement an SBI which is mostly the combination of OCSs and metacognitive model. The project implementation falls into four meeting with the focus described as follows (1) Introducing OCSs and metacognitive training model, (2) Employing help-seeking strategies and modified interaction strategies through conversation tasks, (3) Employing modified output strategies and time-gaining strategies through conversation tasks and (4) Employing maintenance strategies and self-solving strategies through conversation tasks. This project is expected to give best practice to the English teachers of partner school as a part of teaching professionalism improvement and development.